Actualización clínica y terapéutica de la polimialgia reumática. - Vallejo Naranjo, Mishell Dayana (2024)
Polymyalgia rheumatica is a chronic inflammatory disease that is 2 to 3 times more common in women and is a significant health concern among patients over 50 years of age. However, its etiology, despite significant exploration, remains unknown. It is characterized by inflammation, pain, and morning stiffness in the shoulders, neck, and waist, pelvic pain, as well as general symptoms such as fatigue, fever, and weight loss. The pathophysiology may be an abnormal autoimmune response, which would mainly involve T cells. An increase in the same T helper cells 17 was observed, and a combined decrease in regulatory T cells was also discovered. The memory T lymphocytes contribute to the PMR inflammation cascade thanks to their ability to produce interferon and tumor necrosis factor abundantly. Cytokines Proinflammatory cells could be involved in the pathogenesis of PMR. Patients also frequently report difficulty in movement, which is usually bilateral in most cases. Around 40 to 50% of patients have low-grade fevers, lethargy, asthenia, anorexia, and weight loss. During the physical examination, it is important to emphasize Active mobility, especially in shoulder abduction, which is usually limited due to sensitivity. While there is no gold standard for the diagnosis of PMR, healthcare professionals play a crucial role in the process. Unlike other rheumatic syndromes, there are no specific clinical manifestations or other laboratory findings in PMR, making diagnosis a challenge. However, with their expertise, healthcare professionals can diagnose PMR based on a combination of new-onset symptoms of shoulder stiffness and pain in people over 50 years of age, elevated VSG, and CRP. Emphasizing patient education is crucial. By providing personalized instructions about the disease, its impact, treatment, comorbidities, disease predictors, and exercises, healthcare professionals can empower their patients to take an active role in managing their condition.